Useful Database of Effective Gettering Sites for Metal Impurities in Si Wafers with First Principles Calculation. (1st January 2015) - Shirasawa, Sho; Sueoka, Koji; Yamaguchi, Tadashi; Maekawa, Kazuyoshi
Abstract : Fe, Ni, and Cu atoms diffuse very quickly in Si and are the main targets for metal gettering. W, Hf, and Mo atoms, for example, which diffuse very slowly in Si have also recently become gettering targets in addition to these metals. Therefore, proximity gettering techniques by using ion implantation are also being considered. Not only implanted elements but intrinsic point defects exist and form several complexes after the heat-treatment for Si crystal recovery. This research systematically investigated the binding energy of twelve important metals (Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Hf, Ta, and W) with dopants (B, C, P, As, and F) and their complexes with intrinsic point defects (vacancies ( V s) and self-interstitials ( I s)) by using first principles calculation. The database should be useful in designing effective gettering sites for metal impurities partially covering proximity gettering in LSI manufacturing processes.